Thioaldehydes from Aldehyde–Hydrogen Sulfide Interaction Under Organocatalysis. Issue 11 (14th December 2016) - Kumar, Manoj; Francisco, Joseph S.
Abstract: Thioaldehydes are an important class of sulfur compounds involved in atmospheric, synthetic organic, and biological chemistry. Traditionally, they are believed to be formed by the nucleophilic attack of bisulfide anion on the carbonyl compounds. Herein, we suggest a new mechanism that does not require the formation of bisulfide anion, but rather involves an interaction between hydrogen sulfide and an aldehyde. Though the uncatalyzed or the water‐catalyzed reactions involve high barriers, the formic acid‐catalyzed reactions involve moderate barriers that should be accessible in planetary atmospheres. Under acid catalysis, thioaldehydes are formed in a hydrogen‐bonded state, which is at least 6.8 kcal mol −1 more stable than separated product and catalyst. This may have implications for the solution‐phase synthesis of simpler thioaldehydes, which has been a challenge because of their tendency to oligomerize. Another important implication of these results is for the aspartate semialdehyde→aspartate semithioaldehyde conversion, which is a key biosynthetic reaction in methanogen archaea. The unique ability of the active site aspartate or glutamate residue to catalyze hydrosulfidation of semialdehyde may explain catalysis inside these enzymes. Abstract : Atmospheric chemistry : A new mechanism for the formation of thioaldehydes in the atmosphere and enzymes that takes advantage of interaction between an aldehyde and hydrogen sulfide has been proposed. The calculations suggest that organic acids in the atmosphere and aspartate or glutamate residues in enzymes may catalyze these chemistries (see scheme).